Inflammatory Bowel Disease or Not: Importance of Histological Evaluation of Colonic Biopsies, Six Months’ Experience at Chughtai Institute of Pathology - Batool, Farhat; Rathore, Saira; Jahangir, Fizza; Chughtai, Akhtar Sohail; Zaman, Samina (Biological and Clinical Sciences Research Journal, 2025)
Inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic condition characterized by inflammation of the gastrointestinal tract. Objective: The objective of this study was to evaluate the role of histopathological features, such as crypt distortion, mucin depletion, cryptitis, crypt abscesses, and granuloma, in distinguishing IBD from other gastrointestinal disorders and assessing disease activity. Methods: This study is a cross-sectional study conducted at Chughtai Institute of Pathology from 01-OCT-2023 to 10-Mar-2024. A total of 370 patients were enrolled in the study. The sample size was calculated using the WHO sample size calculator. Data collection was conducted through a structured protocol, including patient demographics (age, gender, clinical symptoms), endoscopic findings, and histopathological results from colonic biopsies. Colonoscopy was performed under standard clinical procedures, and tissue samples were taken from the colon during the procedure. Results: Granulomas were present in 25% of Crohn’s disease cases, while cryptitis and mucosal ulceration were observed in 40% and 66% of ulcerative colitis cases, respectively. Crypt abscesses were more common in ulcerative colitis (55%) than in Crohn’s disease (12.5%). Associated infections, including C. difficile, were noted in 3.5% of cases, emphasizing the need for a differential diagnosis. Age distribution varied from 4 to 102 years, with a mean age of 35.9 years. Conclusion: Histological examination remains an essential tool in the diagnosis and differentiation of IBD from other colonic disorders. Granulomas, cryptitis, and crypt abscesses are key features that aid in distinguishing Crohn’s disease from ulcerative colitis. Histopathology also plays a critical role in assessing disease activity and guiding therapeutic decisions.